(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The present investigation commences with a series of preliminary considerations on the bioethics of the commencement of life as practiced by Hindus, with reference to the role of procreation for individual adherents, to comprehend its pertinence within the overarching framework of religious precepts. Moreover, this contribution proffers a delineation of parenting by substitution within the Hindu religion in circumstances of infertility or sterility. The analysis concludes with a discussion of the possibilities offered by Indian legislation for third-party reproduction, and devotes concluding reflections to this topic, which is currently the subject of a wide (not only religious) debate.